Preparation method of low-cation mixed ternary positive electrode single crystal material

By performing strong preoxidation and high-temperature sintering on the precursor of the ternary positive electrode material, the Ni2+ is fully oxidized to Ni3+, the cation mixed discharge problem is solved, the electrochemical performance and stability of the material is improved, the preparation process is simplified and the cost is reduced.

CN120138770APending Publication Date: 2025-06-13ZHEJIANG MEIDU HITRANS LITHIUM BATTERY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510154078.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

There are cationic mixed discharge problems during the preparation and circulation of existing ternary cathode materials, which affects the capacity, rate performance and circulation performance of the material.

Method used

By performing strong preoxidation and strong oxidation process during high-temperature sintering on the ternary precursor, Ni2+ in the material matrix is ​​more fully oxidized to Ni3+, reducing the degree of cation mixing, and combining doping elements to improve the preparation process and mechanical strength of the material.

Benefits of technology

It effectively reduces the degree of cation mixing and discharging of the ternary positive electrode material, improves the electrochemical performance of the material, including charge and discharge capacity, rate performance and cycle life, and simplifies the preparation process and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120138770A_ABST
    Figure CN120138770A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ternary positive electrode materials, and particularly relates to a preparation method of a low-cation mixed ternary positive electrode single crystal material. The preparation method comprises the following steps: uniformly mixing a pre-oxidized precursor, a lithium source and a doping additive, performing high-temperature primary sintering in a strong oxidizing atmosphere, then crushing to obtain a primary sintering base material with a target particle size, and then coating and secondarily sintering the primary sintering base material to obtain a target product. According to the preparation method, Ni < 2 + > in a material matrix is more fully oxidized into Ni < 3 + > through strong pre-oxidation of the ternary precursor and a strong oxidation process during high-temperature sintering, so that the cation mixing degree in the material is further reduced, and the electrochemical performance, including the charge-discharge capacity, the rate capability and the cycle service life, of the single-crystal ternary material is improved. Meanwhile, doping elements are combined, so that the preparation process and the mechanical strength of the material are improved in a targeted manner, and the stability of the material is further improved. Therefore, the method has a wide market application prospect. Meanwhile, the preparation method is simple, and industrial large-scale production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ternary cathode materials, and particularly relates to a preparation method of a ternary cathode single crystal material with low cation mixing disorder. Background Art

[0002] Compared with other battery technologies, lithium-ion batteries have been widely used in fields such as 3C digital products, power tools, electric vehicles, and electrochemical energy storage due to their advantages of high energy density, small size, and long cycle life. As one of the core components of lithium-ion batteries, the cathode material has a great influence on the performance of lithium-ion batteries. Lithium nickel cobalt manganese (aluminum) oxide (NCM / NCA) ternary cathode materials have become one of the mainstream cathode materials in today's lithium batteries due to their certain advantages in energy density, high and low temperature rate performance.

[0003] However, due to the 2+ particle radius of Ni and the + particle radius of Li, there is a certain degree of Ni 2+ ion occupying the Li + crystal cell position during the preparation and cycling of ternary materials, that is, cation mixing disorder. Cation mixing disorder has varying degrees of influence on the capacity, rate performance, and cycling performance of the material. To reduce the degree of cation mixing disorder during material preparation, the current conventional methods are as follows: ① Increase the oxygen concentration in the sintering atmosphere: sintering ternary materials in a high oxygen partial pressure atmosphere can partially inhibit the process of Ni 3+ ions turning into Ni 2+ ions; ② Cation doping: introduce cation doping (such as Na + , Mg 2+ , Al 3+ , etc.); ③ Negative valence anion doping: introduce negative valence anion doping (such as F - ). The above methods can all reduce the degree of cation mixing disorder of the material to a certain extent and improve the electrochemical performance of the material, but the uniformity and consistency of doping pose certain requirements for the material preparation process. Therefore, it is necessary to develop a more effective and economical preparation method for cathode materials to reduce the degree of cation mixing disorder of the prepared ternary materials, especially high-nickel materials. Summary of the Invention

[0004] The purpose of the present invention is to solve the existing technical problems mentioned above and provide a preparation method of a ternary cathode single crystal material with low cation mixing disorder. The present invention, through the strong pre-oxidation of the ternary precursor and the strong oxidation process during high-temperature sintering, oxidizes the Ni in the material matrix 2+ more fully into Ni 3+, thereby further reducing the degree of cation mixing in the material and improving the electrochemical performance of the single-crystal ternary material, including charge-discharge capacity, rate performance, and cycle service life. At the same time, combined with doping elements, the preparation process of the material and the mechanical strength of the material are targeted improved, thereby improving the stability of the material. Therefore, it has broad market application prospects. At the same time, the preparation method of the present invention is simple and easy to be applied in large-scale industrial production.

[0005] In order to achieve the above-mentioned invention purpose, the present invention provides the following technical solutions:

[0006] A preparation method of a low-cation-mixing ternary cathode single-crystal material, the chemical formula of the material is LiNi x Co y M 1-x-y A z O 2 , M = Mn or Al, where 0.6 ≤ x < 0.9, 0.01 ≤ y ≤ 0.3, x + y < 1, 0 < z ≤ 0.05; A is a doping element and / or a coating element, selected from one or a combination of elements such as Al, Zr, Sr, Y, W, La, Nb, Ta, B, Ti, Co; the preparation method is to mix the pre-oxidized precursor, lithium source, and doping additive evenly, and then under a strong oxidation atmosphere, perform a high-temperature one-time sintering, and then obtain a matrix material of the target particle size through air-flow crushing. The matrix material after the first sintering is then coated and subjected to a second sintering to obtain the target product. Subsequently, through conventional post-treatment steps such as coarse crushing, sieving, and iron removal, the final finished product to be packaged can be obtained.

[0007] Preferably, in the chemical formula of the material, x = 0.6 - 0.8, y = 0.01 - 0.3; more preferably, x = 0.65 - 0.7, y = 0.05 - 0.08;

[0008] Preferably, the doping element A is selected from at least one of Al, Zr, Sr, and W, more preferably at least one of Zr and Sr; more preferably, the doping element is doped into the cathode material through the corresponding oxide and / or hydroxide and / or carbonate. In conventional technologies, the degree of cation mixing can be reduced by doping means (for example, doping ions occupy the Li + site, and / or the transition metal ion site, and / or the oxygen site); in the present invention, through the combination of doping elements and the material preparation process, the main functions of doping are: improving the degree of single crystallization of the material; using the strong chemical bond between the doping element and the O element to improve the mechanical strength of the material; thereby improving the stability of the material.

[0009] Preferably, for the pre-oxidized precursor, its preparation process is to introduce a strong oxidizing substance into the system during the aging stage in the later stage of the co-precipitation of the ternary precursor. The strong oxidizing substance can be a liquid or a gas to partially oxidize Ni in the precursor2+ ., More preferably, the chemical formula of the precursor is (Ni x Co y M 1-x-y )OOH, where M = Mn / Al, 0.6 ≤ x < 0.9, 0.01 ≤ y ≤ 0.3, and x + y < 1. More preferably, the strong oxidizing substances include KMnO 4 , HClO, H 2 O 2 and O 3 at least one of, more preferably H 2 O 2 , O 3 at least one of. More preferably, during the aging process of the precursor, an oxygen-ozone mixed gas with a flow rate of 1-10 m 3 / h (where the volume ratio of ozone is about 10 ± 5%) is introduced, and the introduction time is 3-6 h.

[0010] Preferably, the D50 particle size of the pre-oxidized precursor is 2-5 μm, preferably 3.0-3.5 μm; the specific surface area of the precursor is 6-15 m 2 / g, preferably 8-12 m 2 / g.

[0011] Preferably, in the preparation method, the feeding relationship between the lithium source and the pre-oxidized precursor is: the lithium source is calculated as Li, and the pre-oxidized precursor is calculated as Me (Me = Ni + Co + M, where M = Mn / Al), that is, the molar ratio Li:Me = 1.00-1.06:1, more preferably Li / Me = 1.045-1.05.

[0012] Preferably, in the preparation method, the lithium source used is selected from at least one of lithium carbonate, lithium acetate, and lithium hydroxide, and more preferably lithium hydroxide is used.

[0013] Preferably, in the preparation method, the doping additive used is selected from oxides and / or hydroxides and / or carbonates containing doping elements, and the doping elements include at least one of Al, Zr, Sr, Y, W, La, Nb, Ta, B, and Ti; more preferably, the feeding amount of the doping additive is 500-5000 ppm based on the doping element;

[0014] More preferably, the doping additive is selected from oxides containing Zr and / or hydroxides containing Sr, where the doping amount of Zr is 1000-3000 ppm, preferably 2000-2500 ppm; the doping amount of Sr is 500 ppm-1500 ppm, preferably 500-800 ppm.

[0015] Preferably, in the preparation method, the primary sintering temperature is 800 - 1000 °C, preferably 900 - 950 °C; the heating rate for the first sintering is 1 - 10 °C / min, preferably 2 - 5 °C / min; the holding time at the sintering temperature for the primary sintering is 6 - 30 h, preferably 8 - 20 h, more preferably 8 - 12 h. More preferably, after the primary sintering is completed, it is cooled in the furnace.

[0016] Preferably, in the preparation method, the strong oxidation atmosphere for the primary sintering is controlled as follows: ①. In the heating stage (about 3 - 6 h), a pure oxygen atmosphere is introduced; ②. The atmosphere control conditions for the high-temperature stage of the primary sintering (i.e., the holding stage after heating to the sintering temperature) are that a mixed gas of ozone and oxygen is introduced in the front section of the high-temperature zone. The volume ratio of ozone gas in the mixed gas is 1 - 4%, preferably 3 - 4%, and the introduction time is 1 - 6 h, preferably 2 - 3 h; a pure oxygen atmosphere is introduced for the remaining time in the high-temperature stage; ③. In the cooling stage (5 - 7 h), a pure oxygen atmosphere is introduced.

[0017] Preferably, in the preparation method, the target particle size of the material after air jet milling is D50 within 3.0 - 5.0 μm, more preferably 3.5 - 4.0 μm.

[0018] Preferably, in the preparation method, the coating process is as follows: ①. Add the matrix material after the first sintering and a certain amount of coating additives into a high-speed mixer and carry out high-speed stirring coating; the rotation speed of the mixer blades is 300 - 500 rpm, preferably 450 rpm, and the coating time is 15 - 35 min, preferably 25 min; ②. The coating additives used are at least one selected from oxides and / or hydroxides containing elements such as Al, Zr, Sr, Y, W, La, Nb, Ta, B, Ti, and Co. The feeding amount of the coating additives is basically in the range of 500 - 3000 ppm in terms of the coating elements; preferably, it is at least one of the corresponding oxides containing Al and / or W, where the coating amount of Al is 1000 - 3000 ppm, preferably 1000 - 1500 ppm, and the coating amount of W is 2000 - 5000 ppm, preferably 2500 - 3000 ppm.

[0019] Preferably, in the preparation method, the secondary sintering temperature is 300 - 600 °C, preferably 450 - 500 °C; the heating rate is 1 - 10 °C / min, preferably 2 - 3 °C / min; the high-temperature sintering time is 5 - 20 h, preferably 7 - 10 h; the atmosphere for the second sintering is at least one of compressed air and oxygen excluding carbon dioxide and moisture, preferably an oxygen atmosphere.

[0020] Preferably, the particle size D50 of the target product material obtained after the second sintering is 3.0 - 5.0 μm, more preferably 3.5 - 4.0 μm; the material has a single crystal morphology, and the average size of the single crystal particles of the material is 1.0 - 2.0 μm, more preferably 1.3 - 1.5 μm.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] (1) The ternary cathode single crystal material prepared by the present invention through strong pre - oxidation of the precursor and sintering in a strong oxidation atmosphere has certain advantages in capacity, rate performance and cycle performance compared with the ternary cathode single crystal material of the same proportion prepared by the conventional process. Among them:

[0023] ① The 0.1C coin - cell capacity is increased by 2 - 5 mAh / g compared with the single - crystal product of the same proportion (NCM) by the conventional process;

[0024] ② Its rate performance (the ratio of the discharge capacity at 3.0C to the discharge capacity at 0.1C, i.e., Capacity - 3.0C / 0.1C) is increased by 2 - 3% compared with the product of the same proportion (NCM) by the conventional process;

[0025] ③ Its cycle performance (the capacity retention rate after 50 charge - discharge cycles at 1.0C in coin - cell) is increased by 2 - 3% compared with the product of the same proportion (NCM) by the conventional process;

[0026] The improvement of the above - mentioned electrochemical performance mainly comes from the fact that Ni 2+ in the material is fully oxidized to Ni 3+ , reducing the occupancy of Ni 2+ in the Li + site, thereby reducing the degree of cation mixing, and further improving the Li + transport process in the material matrix, and improving the discharge capacity and rate performance of the material; on the other hand, the reduction of the degree of cation mixing improves the structural consistency of the material, and combined with the subsequent coating process, the cycle service life of the material is improved. The improvement of the oxidation efficiency of Ni 2+ in the material mainly comes from the following two processes: 1) Strong pre - oxidation of the precursor: During the aging stage of precursor preparation, a certain volume of strong oxidizing gases or liquids such as O 3 is introduced, which can oxidize part of the Ni 2+ in the material into Ni 3+ in advance; 2) Strong oxidation atmosphere during high - temperature sintering: During the high - temperature sintering process, a certain volume of strong oxidizing O 3 gas is introduced to fully oxidize the Ni 2+ in the material matrix into Ni 3+ , thereby reducing the degree of cation mixing in the material;

[0027] (2) Shorten the high-temperature sintering time and reduce the production and processing costs of the material. During the preparation of ternary materials, the materials generally need to be continuously sintered at high temperature for a long time (more than 12 hours) to obtain primary grains of sufficient size and a ternary cathode material with an appropriate degree of cation mixing. After using the precursor strong pre-oxidation and strong oxidation atmosphere sintering process, the high-temperature sintering time can be significantly shortened, and the degree of cation mixing can be further reduced, effectively reducing the production cost. Description of the Drawings

[0028] Figure 1 It is the electron microscope image of the finished product of Example 1;

[0029] Figure 2 It is the process flow chart of Example 1;

[0030] Figure 3 It is the XRD pattern of the finished products of Examples 1-4;

[0031] Figure 4 It is the XRD pattern of the finished products of Examples 5-8. Detailed Embodiments

[0032] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation mode of the present invention will be further clearly, completely and detailedly described below through specific embodiments and in combination with the drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and the detailed implementation modes and specific operation processes are given, but they are only a part of the embodiments of the present invention, not all of the embodiments. The specific implementation modes described are only used to illustrate and explain the present invention and do not limit the present invention. Based on the embodiments in the present invention, all other implementation modes obtained by those of ordinary skill in the art without creative work belong to the scope of protection of the present invention.

[0033] In the embodiments of the present invention, the experimental methods and conditions used are all conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the embodiments can be obtained from commercial channels or prepared by conventional methods unless otherwise specified. The reaction conditions reflected in the content of the present invention can all realize the reactions and obtain the products with expected effects. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical scheme of the present invention.

[0034] Example 1:

[0035] This example provides a preparation method of a low-cation-mixing ternary cathode single crystal material, including the following steps:

[0036] (1) Prepare pre-oxidized Ni 0.65 Co 0.07Mn 0.28 The method for preparing the MnO(OH) precursor is as follows:

[0037] Prepare a mixed solution (feed solution) of nickel cobalt manganese sulfate with a concentration of 1.8 mol / L and a molar ratio of Ni:Co:Mn = 65:7:28 by using nickel sulfate NiSO 4 .6H 2 O, cobalt sulfate CoSO 4 .7H 2 O, and manganese sulfate MnSO 4 .H 2 O; prepare a 5 mol / L sodium hydroxide solution and a 10 mol / L ammonia water solution;

[0038] The co-precipitation process can adopt conventional reaction steps and conditions in the art. Specifically, it can be referred to as follows: Add clear water to the precursor reaction kettle to the overflow port position, introduce nitrogen for 4 h and heat up to 60 °C, introduce the ammonia water solution, control the ammonia concentration in the reaction kettle at 2.5 - 3.0 g / L, and start the concentrator at the same time; Continuously add the mixed solution of nickel cobalt manganese sulfate to the reaction kettle at a liquid medicine flow rate of 45 L / h, and at the same time control the pH value of the solution between 10.2 - 10.5 by adjusting the flow rate of the sodium hydroxide solution, and control the ammonia concentration in the slurry at 2.5 - 3.0 g / L by adjusting the flow rate of the ammonia water solution; The stirring speed of the reaction kettle is 150 rpm; When the particle size of the precursor reaches 3.0 - 3.5 μm, transfer the slurry to the aging kettle for aging;

[0039] The aging process is carried out in the presence of strong oxidants until the slurry turns brownish gray; More preferably, during the aging process of this embodiment, an oxygen atmosphere containing 10% by volume of ozone is continuously introduced into the aging kettle at a flow rate of 5 m 2 / h until the slurry turns brownish gray (about 3 h); Then press-filter the slurry, and then wash the prepared precursor with a 5 mol / L NaOH solution and pure water at 65 °C. After drying, sieving, and demagnetization, a pre-oxidized precursor is obtained;

[0040] (2) The method for preparing the single-crystal cathode material is as follows:

[0041] High-speed mix the pre-oxidized precursor, lithium hydroxide, and the first-burning doping additive. Among them, 3000 g of the precursor is weighed, 1345 g of LiOH.H 2 O is weighed, 9.69 g of zirconia is weighed; 3.46 g of strontium hydroxide is weighed. Add the above materials to the high-speed mixer, with a high speed of 45 Hz and stir for 25 min;

[0042] Load 2000 g of the mixed materials into a sagger and conduct the first sintering in a box-type furnace. The sintering regime is as follows: heat up to the target temperature of 940 °C at a rate of 3 °C / min, and introduce pure oxygen gas throughout the heating stage (flow rate: 2 m 3 / h); keep it at a constant temperature for 10 h in the high-temperature stage. Among them, the oxygen introduced in the first 2 h is processed by an ozone generator, and its ozone concentration is 4% (volume ratio). Pure oxygen gas is introduced in the subsequent 8 h, and the flow rate is 2 m 3 / h; after the high-temperature holding stage, enter the natural cooling stage, and continuously introduce 2 m 3 / h of pure oxygen gas until the temperature drops below 100 °C. After the furnace temperature drops below 100 °C, the materials can be taken out of the furnace, crushed, and sieved to obtain the finished product of the first single-crystal sintering;

[0043] Conduct high-speed mixing of the finished product of the first sintering and the additives for the second sintering coating. Among them, weigh 700 g of the finished product of the first sintering, 2.00 g of alumina, and 2.84 g of tungsten oxide. Add the above materials to a high-speed mixer, with a high speed of 45 Hz and mixing for 25 min;

[0044] Load 500 g of the mixed materials into a sagger and conduct sintering in a box-type furnace. The sintering regime is as follows: heat up to the target temperature of 460 °C at a rate of 3 °C / h, keep it at a constant temperature for 10 h, and then conduct natural cooling; introduce compressed air with carbon dioxide and water removed throughout the process, and the flow rate of the compressed air is 2 m 3 / h. After the furnace temperature drops below 100 °C, the materials can be taken out of the furnace, sieved, de-ironed, and packaged. Finally, obtain the finished product of this example.

[0045] Example 2 - 10:

[0046] The specific implementation process of Example 2 - 10 is the same as that of Example 1. The summary of the changes in some parameters is shown in Table 1 below:

[0047] Table 1 is the summary table of the process parameters of Examples 1 - 10

[0048]

[0049] Test example:

[0050] (1) The surface residual lithium, particle size, BET, and the content of each component element of the samples in Examples 1 - 10 are tested using acid-base titration, Malvern MS3000 laser particle size analyzer, specific surface area analyzer, and inductively coupled plasma emission spectrometer (ICP), respectively;

[0051] (2) The structural analysis of the samples in Examples 1 - 10 is tested and analyzed using an X-ray diffractometer (Bruker D8 ADVANCE A25).

[0052] (3) The surface morphology of the samples of Examples 1-10 was tested by a scanning electron microscope (JSM-IT200(BU)).

[0053] (4) The electrical properties of Examples 1-10 were tested as follows: The ternary single-crystal products obtained in the examples were mixed with a binder and a conductive agent SupperP in a ratio of 80:10:10 wt%, and thoroughly mixed evenly with a grinding pestle. The powder was dissolved in N-ethylpyrrolidone and stirred at room temperature for 24 h. Then, the slurry was coated on the surface of aluminum foil and vacuum-dried at 120 °C for 48 h. After that, the coated aluminum foil was cut into circular pieces with a diameter of about 15 mm as the positive electrode of a lithium-ion battery. A lithium-ion battery electrolyte (EC:EMC:DMC = 1:1:1, LiPF 6 with a concentration of 1 mol / L) and a counter electrode metal lithium foil were used to form an RC2030 type button battery in a glove box according to the positive electrode material, electrolyte, battery separator, electrolyte, negative electrode material, pressure plate and spring. Constant current charge and discharge tests were carried out in a Neware battery test system. The cycle performance was tested at a temperature of 25 °C, a rate of 1 C, and a charge and discharge voltage range of 2.8-4.3 V for 50 cycles.

[0054] (5) According to the test data analysis:

[0055] The test results are shown in Tables 2 and 3 below:

[0056] Table 2 is a summary table of the physical and chemical indexes of Examples 1-10

[0057]

[0058] Table 3 is a summary table of the unit cell parameters, cation mixing degree and electrical properties of the materials of Examples 1-10

[0059]

[0060] It can be seen from the above content that:

[0061] ①: As can be seen from Examples 1-10, the strong oxidizing atmosphere in the precursor pre-oxidation and primary sintering processes has little effect on the physical and chemical indexes of the materials.

[0062] ②: By comparing Examples 1 and 2, it can be seen that the strong oxidation time in the first sintering process needs to be controlled above a certain range. Too short a strong oxidation atmosphere sintering time is not sufficient to fully oxidize Ni in the matrix to Ni 2+ fully, thus reducing the cation mixing effect and having a certain impact on the capacity, rate and cycle performance of the material. 3+

[0063] ③: It can be seen from the comparison of Examples 1, 3, and 4 that when the sintering time in a strong oxidation atmosphere exceeds a certain time, the effect of reducing the cation mixing in the material decreases; on the other hand, sintering in a strong oxidation atmosphere can, to a certain extent, reduce the high-temperature sintering time without affecting the physical and chemical properties and electrical properties of the material, thereby reducing the processing cost of the material.

[0064] ④: Through the comparison of Examples 5, 6, 7, and 8, the actual effects of precursor pre-oxidation and strong oxidation atmosphere in the first firing on reducing the degree of cation mixing in the material and improving the electrical properties of the material were confirmed.

[0065] ⑤: It can be seen from the comparison of Examples 9 and 10 that in other materials with Ni content systems, precursor pre-oxidation and sintering in a strong oxidation atmosphere can play the same role.

[0066] The above-described embodiments are only preferred solutions of the present invention, and do not impose any form of limitation on the present invention. There are other variations and modifications without exceeding the technical solutions described in the claims.

Claims

1. A method for preparing a low-cation mixed ternary positive electrode single crystal material, characterized in that: The chemical formula of the material is LiNi x Co y M 1-x-y A z O2, where M = Mn or Al, 0.6 ≤ x < 0.9, 0.01 ≤ y ≤ 0.3, x + y < 1, 0 < z ≤ 0.05; A is a doping element and / or a coating element, selected from one or a combination of elements such as Al, Zr, Sr, Y, W, La, Nb, Ta, B, Ti, Co; the preparation method is to uniformly mix the pre-oxidized precursor, lithium source, and doping additive, and then perform a one-time high-temperature sintering in a strong oxidation atmosphere, and then obtain a matrix material of the target particle size after pulverization. The matrix material after the first sintering is then coated and sintered for the second time to obtain the target product.

2. The method for preparing a low-cation mixed ternary positive electrode single crystal material according to claim 1, characterized in that: The preparation process of the pre-oxidized precursor is to introduce a strong oxidizing substance into the system during the aging stage of the ternary precursor co-precipitation to partially oxidize Ni in the precursor. 2+ .

3. The method for preparing a low-cation mixed ternary positive electrode single crystal material according to claim 1, characterized in that: The feeding relationship between the lithium source and the pre-oxidized precursor is: the lithium source is calculated as Li, the pre-oxidized precursor is calculated as Me, the molar ratio Li:Me=1.00-1.06:1, wherein Me=Ni+Co+M, M=Mn / Al; the lithium source is selected from at least one of lithium carbonate, lithium acetate, and lithium hydroxide.

4. The method for preparing a low-cation mixed ternary positive electrode single crystal material according to claim 1, characterized in that: The doping additive is selected from oxides containing Zr and / or hydroxides containing Sr, wherein the doping amount of Zr is 1000-3000ppm, and the doping amount of Sr is 500ppm-1500ppm.

5. The method for preparing a low-cation mixed ternary positive electrode single crystal material according to claim 1, characterized in that: The primary sintering temperature is 800-1000°C, the heating rate is 1-10°C / min, and the primary high-temperature sintering time is 6-30h.

6. The method for preparing a low-cation mixed ternary positive electrode single crystal material according to claim 5, characterized in that: The strong oxidizing atmosphere of the primary sintering is controlled as follows: ①, introducing pure oxygen atmosphere during the heating stage; ②, the atmosphere control condition of the high temperature stage of the primary sintering is that pure oxygen gas treated by an ozone generator is introduced into the front section of the high temperature zone, wherein the volume proportion of ozone gas is 1-4%, and the introduction time is 1-6h; pure oxygen atmosphere is introduced during the remaining time of the high temperature stage; ③, during the cooling stage, pure oxygen atmosphere is introduced.

7. The method for preparing a low-cation mixed ternary positive electrode single crystal material according to claim 1, characterized in that: The target particle size of the crushed material is 3.0-5.0 μm.

8. The method for preparing a low-cation mixed ternary positive electrode single crystal material according to claim 1, characterized in that: The coating process is as follows: ①, adding the monostyrene matrix material and the coating additive into a high-speed mixer for high-speed stirring and coating; the blade speed of the high-speed mixer is 300-500rpm, and the coating time is 15-35min; ②, the coating additive used is at least one selected from oxides and / or hydroxides containing Al, Zr, Sr, Y, W, La, Nb, Ta, B, Ti, and Co elements.

9. The method for preparing a low-cation mixed ternary positive electrode single crystal material according to claim 8, characterized in that: The coating additive is an oxide containing Al and / or an oxide containing W, wherein the coating amount of Al is 1000-3000 ppm, and the coating amount of W is 2000-5000 ppm.

10. The method for preparing a low-cation mixed ternary positive electrode single crystal material according to claim 1, characterized in that: The secondary sintering temperature is 300-600°C, the heating rate is 1-10°C / min, the high-temperature sintering time is 5-20h, and the secondary sintering atmosphere is at least one of compressed air and oxygen except for carbon dioxide and moisture.

Citation Information

Cited By

  • Layered structure regulation and control method of ternary battery positive electrode precursor

    CN121063602A